Pengaruh Discovery Learning dan Ekspositoy Learning terhadap Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar Negeri Kota Samarinda - Santoso, Agus; Nasir, Muhammad (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2016)
This research is from the concept of strategies discovery learning and ekspository learning to student learning outcomes. Discovery learning is learning-centered to student where the subject matter of Islamic education has been engineered by the teacher. And ekspository learning is learning that focused on the teachers that are the subject matter of Islamic education is taught by the teacher's knowledge. While the learning outcome is the result of student learning as evidenced by the form of report cards. This research is quantitative with associative approach. Informant entire fifth grade elementary school students in the city of Samarinda. The data collected with using questionnaires, observation and documentation. While the analysis used phases check, the process of identification, classification process, mean test, correlation and t-test. The results of this research is there was a significant effect of discovery learning and ekspository learning together on learning outcomes of students in the subjects of Islamic education in public elementary school Samarinda.